High-strength Engineered Biomaterials Study and Development Needs in China - Qian Wang; Xin Feng (BioResources, 2024)
Engineered biomaterials play a crucial role in the construction industry. The study and development of engineered biomaterials with high-strength are necessary to fulfill the construction requirements for medium and high-rise buildings and long-span bridges. Further promoting the localization of high-strength engineered biomaterials is crucial in terms of reducing CO2 emissions, effectively utilizing land resources, and taking into account the unique structure of forest resources in China. The goal of this modification is to satisfy the rising demand for eco-friendly living spaces.